Process and economic evaluation of an on-board capture system for LNG-fuelled CO2 carriers - Awoyomi, Adeola; Patchigolla, Kumar; Anthony, Edward J. (American Chemical Society, 2019)
Marine pollution is a major problem but one that has to date been largely overlooked; thus, for example, it was not accounted for in the Paris agreement on climate change. Maritime fuel combustion currently contributes to 3% of the annual global greenhouse gas emissions. Nearly all shipping-related emissions occur within 400 km of land, and cause death and increased morbidity to millions of people. The initial greenhouse gas strategy on the reduction of carbon emissions to at least half of its 2008 levels by 2050, adopted by the International Maritime Organization, has the potential to spur on innovations and the use of alternative fuel, enabling the shipping industry to adapt to future challenges. Some zero-emission options such as the use of hydrogen and bio-fuels are considered potential strategies, but currently lack the infrastructure capacity needed to meet the world’s shipping demand. Liquefied natural gas (LNG) has gained substantial interest as a marine fuel because it can comply with the strictest environmental regulations currently in force, and it is often regarded as a future shipping fuel as most newly constructed ships are built to run on it. Although the use of LNG leads to lower CO2 emissions compared to traditional heavy fuel oils (HFOs), there is still a need for further reduction. A solution which can be implemented is that of an on-board marine capture system, also known as ship-based carbon capture. In this study, a process and economic evaluation was carried out on a solvent-based post-combustion capture process for the energy system of a CO2 carrier. A rate-based model was developed, validated and scaled up to process the flue gas from a Wartsila 9L46 DF marine diesel engine. Different modes of operation with respect to engine load and capture rate were analysed in this study and the capture cost was estimated. The cost of CO2 capture was used as an economic index for this study. It was observed via a sensitivity analysis that at 90% capture rate, the cost of capture was at least $117/t. The effect of exhaust gas recycle was also explored and this resulted in a considerable reduction in the capture cost. The exhaust gas waste heat was utilised and was adequate to supply the required energy needed by the reboiler at each capture rate examined. Also, for LNG-fueled CO2 ships, the cold energy obtained while converting the LNG to gas was utilised to liquefy the captured CO2 from the flue gas.
Keywords: On-board carbon capture; maritime carbon capture; zero-emission ships; marine engine propulsion; post-combustion capture